Anisotropy and spin relaxation in the condensed phase - Handsel, J (2016)
Chapter 1 introduces the concept of spin, how spins interact, and how the spin state in a radical pair can affect the outcome of a chemical reaction between the unpaired electrons. The computational methodology for simulating such radical pairs is also discussed. Chapter 2 discusses anisotropy in the singlet recombination yield of a radical pair in a carotenoid-porphyrin-fullerene triad, containing many hyperfine couplings. The singlet yield was calculated as a function of the direction of an applied magnetic field, using symmetry in the molecule to reduce the size of the problem. The symmetry reduction was partially successful, however it was not possible to include all the hyperfine couplings in the molecule. Chapter 3 introduces a radical pair located on a flavin ligand and a tryptophan residue in the protein cryptochrome, and discusses the spin-relaxation mechanism of singlet-triplet dephasing. Magnetic field effect curves, describing the formation of a secondary radical pair as a function of applied magnetic field, were found to be broader in longer-lived radical pairs, due to dephasing caused by spin-selective recombination to the singlet ground state. Additional singlet-triplet dephasing may occur due to hopping of one of the unpaired electrons, between a zone of strong exchange interaction and a zone of negligible exchange interaction, although this is an incomplete description of the spin-relaxation. Chapter 4 discusses the effect of rotational tumbling on spin-relaxation in the flavin-tryptophan radical pair in cryptochrome. Simulations indicated that the resulting modulation of anisotropic hyperfine couplings contributed modestly to spinrelaxation during transient absorption measurements, but was insufficient to explain the lack of an experimental low-field effect, or to explain the width of the experimental magnetic field effect curves as a function of magnetic field strength. Chapter 5 discusses magnetic field effects on the mutual annihilation of a pair of triplet excitons in tetracene and anthracene crystals. The experimental singlet recombination yield was found, for the first time, to be modulated as a function of the direction of a applied magnetic field as weak as 2 mT. Simulations indicated that this anisotropy arose due to the zero field splitting of the electronic state in each triplet exciton. The direction of the external magnetic field altered the singlet component of the eigenstates of the Hamiltonian, and therefore altered the timeaverage of the singlet probability of a triplet exciton pair. This is different to the already established mechanism under a strong magnetic field, where the anisotropy arises from level crossings of eigenstates.